Pengaruh Tingkat Literasi Keuangan, Inovasi Digital, Dan Modal Usaha Terhadap Keberlanjutan Umkm Pada Pelaku Umkm Di Wisata Pantai Pasir Putih Situbondo - Sazicha Iqromi; Retno Endah; Achmad Hasan (Jurnal Ekonomi, Manajemen, Akuntansi dan Keuangan, 2025)
This study aims to analyze the influence of financial literacy, digital innovation, and business capital on the sustainability of Micro, Small, and Medium Enterprises (MSMEs) in the tourist area of Pasir Putih Beach, Situbondo. The research focuses on how these three internal factors explain the resilience and adaptability of MSMEs in facing fluctuating external challenges. A quantitative approach was applied using a survey method. The population consisted of active MSME actors in the tourist area, with a purposive sampling technique and a total of 70 respondents. The research instrument was a structured questionnaire, and the data were analyzed using multiple linear regression with SPSS software.The results indicate that financial literacy has a positive and significant effect on MSME sustainability, meaning that the higher the financial management capability of business actors, the stronger their business sustainability. Digital innovation also shows a positive and significant influence, demonstrating that the use of digital technology in operations and marketing supports MSMEs in surviving and growing in the digital era. Furthermore, business capital has a positive and significant impact, indicating that access to and adequacy of funding is essential to support business growth and expansion. Thus, the three variables are proven to be key determinants in building MSME sustainability in local tourism sectors. This research provides practical implications for policymakers and business practitioners in formulating strategies to strengthen MSMEs based on internal resources.